Ceramic-based surface strengthening agent for underground coal gasification downhole tool, strengthening method and material obtained through strengthening

By using ceramic-based surface reinforcement agent to form high-hardness metal compounds on coal underground gasification tool equipment, the problem of insufficient wear resistance of tool equipment in high temperature and corrosion environments is solved, and its service time is significantly extended.

CN119912264APending Publication Date: 2025-05-02CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311419527.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Coal underground gasification technology has insufficient high temperature and corrosion resistance performance of tools and equipment in high temperature and corrosion-resistant environments, resulting in insufficient service time of the system under high temperature and erosion and wear conditions, limiting the large-scale promotion of technology.

Method used

Ceramic-based surface reinforcement agent, including boron supply agent B4C, activator KBF4, filler SiC and reducer graphite, is used to form high-hardness metal compound M2B through heating and insulation treatment, which significantly improves the high-temperature wear resistance of the material.

Benefits of technology

It significantly improves the high-temperature wear resistance of the material, forming a high-performance reinforced surface layer with a thickness of 0.5-1mm and a hardness of up to 58HRC, extending the service time of the tool equipment under high temperature and erosion and wear conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912264A_ABST
    Figure CN119912264A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of petroleum and natural gas tool equipment materials, and particularly relates to a ceramic-based surface strengthening agent for a coal underground gasification downhole tool, a strengthening method and a material obtained through strengthening. In the reinforcing agent, the mass fraction of the boron supply agent is 8.7%-14.7%, the mass fraction of the activating agent is 49.7%-55.7%, the mass fraction of the filling agent is 11.6%-17.6%, and the mass fraction of the reducing agent is 18.0%-24.0%. According to the reinforcing agent provided by the invention, a high-hardness reinforced layer can be generated on the surface of a reinforced matrix material, and the high-temperature wear resistance of the material surface is remarkably improved on the basis of retaining the yield strength and toughness of the matrix material. In addition, the strengthening process of the base material is not limited by the type, shape and size of the base material, and the application range is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petroleum and natural gas tool equipment materials, and specifically relates to a ceramic-based surface strengthening agent for underground coal gasification downhole tools, a strengthening method and a strengthened material. Background Art

[0002] Underground coal gasification (UCG) technology realizes the closed development of coal underground. The product is a mixed gas composed of multiple combustible components, with no solid waste emissions. It is an emerging clean energy development technology that integrates oil drilling technology, conventional coal mining technology and coal-to-gas technology. The main body of underground coal gasification technology consists of several key technologies: coal mine resource site selection, gasification furnace construction, gasification agent and gasification tool equipment research and development, and raw coal gas surface treatment. Domestic UCG technology is still in the industrial test stage as a whole. It has not achieved real industrialization and has not formed a complete industrial chain.

[0003] The most important reason for limiting the large-scale promotion of UCG technology is the key technology to ensure the safe, stable, smooth and efficient operation of the entire underground coal gasification process. It is mainly reflected in the following aspects: First, in the "controlled injection point retreat" process that has been basically mature, the coal seam combustion gasification, the front end of the horizontal well and the bottom of the production well are the weakest links in the entire underground coal gasification channel. The gasification channel equipment is at a high temperature of about 800°C for a long time, and the raw coal gas flowing through contains complex corrosive media such as CO2 and H2S. Combined with high temperature conditions, it is a great test for the high temperature resistance and corrosion resistance of related tools and equipment; second, high-temperature gas-borne particle erosion and wear is one of the harsh working conditions in the underground coal gasification process. Its characteristics are similar to the working environment of aircraft engines, mainly high temperature, abrasive high-speed micro-cutting, and it is also a great test for the high temperature strength and high temperature wear resistance of the material. Based on the working conditions of the underground coal gasification channel, the present invention develops a new type of surface-enhanced high-temperature structural material to ensure that the entire system has sufficient service time under high temperature and erosion and wear conditions, so as to promote the domestic underground coal gasification technology towards industrialization and scale. Summary of the invention

[0004] In order to solve the deficiencies of the prior art, the present invention provides a ceramic-based surface strengthening agent for underground coal gasification downhole tools, a strengthening method and a strengthened material. The strengthening agent provided by the present invention can generate a high-hardness strengthening layer on the surface of the strengthened base material, and significantly improve the high-temperature wear resistance of the material surface on the basis of retaining the yield strength and toughness of the base material. In addition, the strengthening process for the base material is not limited by the type, shape and size of the base material, and has a wide range of applications.

[0005] The technical solution provided by the present invention is as follows:

[0006] A ceramic-based surface strengthening agent for underground coal gasification downhole tools comprises the following components in mass fractions: a boron supply agent in a mass fraction of 8.7%-14.7%, an activator in a mass fraction of 49.7%-55.7%, a filler in a mass fraction of 11.6%-17.6%, and a reducing agent in a mass fraction of 18.0%-24.0%.

[0007] Specifically, the boron supplying agent is B4C.

[0008] In the present invention, the activator reacts with the reductant to obtain products such as boron trifluoride, which then react with B4C to convert the B element into an active free state of B atoms, thereby forming a high-hardness metal compound M2B (M represents Fe, Cr or Mo element) with Fe, Cr or Mo elements in the matrix material. The boron supply agent can continuously provide B elements for entering the surface of the matrix material during the strengthening treatment heating and heat preservation process, so the present invention selects the ceramic-based compound B4C as the boron supply agent. According to the molar ratio of the reactants and the products in each reaction formula, the allowable content range of the boron supply agent is 8.7%-14.7%.

[0009] Specifically, the activator is KBF4.

[0010] In the process of strengthening treatment, the escape and diffusion of the B element in the boron supply agent need to be mobilized and converted, which can be achieved by reacting the activator with the reductant to obtain products such as boron trifluoride, and then reacting with B4C. The presence of the activator ensures that the diffusion efficiency of the B element in the boron supply agent is greatly improved during the heating and heat preservation process. The present invention uses a strong oxidizing salt KBF4 as an activator, and the allowable content range is 49.7-55.7%.

[0011] Specifically, the filler is SiC, SiO2 or Al2O3, preferably SiC, because it has better high temperature stability and lower cost.

[0012] In the present invention, since oxygen is required in the strengthening process, a filler needs to be added to the strengthening agent to ensure that it is loose and easy to fully contact with air. The present invention uses high temperature resistant materials such as SiC as fillers, and the allowed content range is 11.6-17.6%. Compared with other fillers, SiC has advantages in chemical stability and cost.

[0013] Specifically, the reducing agent is graphite or activated carbon, preferably graphite, because graphite has a higher C content and a slower reaction rate with O2 at high temperature.

[0014] In the present invention, before the B element in the boron supply agent is converted into a free B atom, a B-containing intermediate product, such as BF2, is first generated. The B intermediate product needs to react with a reducing agent to convert the B element into the final free B atom. In addition, the reducing agent can also directly react with part of the boron supply agent, thereby having the effect of improving the utilization efficiency of the B element in the boron supply agent. The present invention uses graphite as a reducing agent, and the allowable content range is 18.0-24.0%. Graphite and other reducing agents have the advantages of stable chemical properties and a relatively stable reaction rate with O2.

[0015] The reaction equation of B4C, KBF4 and graphite is as follows:

[0016] 2KBF4+B4C+2O2+C=K2O+4BF2↑+2[B]+2CO↑

[0017] The present invention also provides a method for strengthening an alloy matrix, comprising the following steps: wrapping the alloy matrix with a ceramic-based surface strengthener for underground coal gasification downhole tools, and then heating and keeping the temperature at 950-1050° C. for 3-5 hours, preferably 4 hours.

[0018] The strengthening treatment process of the present invention is easy to operate, does not require any protective atmosphere, and can be carried out only in the atmospheric atmosphere. The base material does not need to undergo fine processing pretreatment such as fine grinding and polishing before treatment, and can be carried out after simply cleaning the surface. The workpiece after the strengthening treatment does not need further heat treatment, and has a wide range of applications.

[0019] Specifically, the alloy matrix is ​​a nickel-based high-temperature alloy, a cobalt-based high-temperature alloy or a heat-resistant steel.

[0020] The strengthening process of the base material of the present invention is not limited by the type, shape and size of the base material and has a wide application range.

[0021] The present invention also provides a material strengthened according to the above method, comprising an alloy matrix and a strengthening layer on the surface.

[0022] Specifically, the strengthening layer includes a high-hardness metal compound M2B formed by B and Fe, Cr or Mo elements, where M is Fe, Cr or Mo element.

[0023] Specifically, the thickness of the strengthening layer is 0.5-1 mm.

[0024] Because the present invention needs to cope with the harsh high-temperature wear conditions of underground coal gasification channels in the long term, it needs to achieve a thickness of 0.5-1mm to meet the integrity requirements of gasification tools and equipment throughout the entire life cycle.

[0025] Specifically, the hardness of the strengthening layer is greater than or equal to 58HRC.

[0026] The ceramic-based surface strengthener for underground coal gasification downhole tools provided by the present invention has the performance characteristics of significant strengthening effect, wide application range, high process freedom, etc. After using the strengthener to carry out surface strengthening treatment on various alloys containing Fe, Cr or Mo elements, a high-performance strengthened surface layer with a thickness of 0.5-1mm and a hardness of up to 58HRC can be obtained on the alloy surface. Compared with similar process technologies, the thickness and hardness of the strengthening layer are at a significantly leading level. The alloy after treatment has the excellent high-temperature yield strength and toughness level of high-temperature alloys and the high hardness and excellent wear resistance of metal-based wear-resistant materials, while the resistance to high-temperature oxidation is further improved. The performance of the high-temperature resistant strengthening layer is sufficient to withstand various high-temperature particle-containing fluid erosion and wear underground working conditions such as underground coal gasification. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the matrix material and reinforcing agent loading method in each embodiment.

[0028] Figure 2 It is a state diagram of the samples after heating and heat preservation in each embodiment.

[0029] Figure 3 This is the EDS analysis result of the strengthening layer of Example 1. DETAILED DESCRIPTION

[0030] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0031] Embodiment 1:

[0032] The technical solution of the present invention is used to perform surface strengthening treatment on the nickel-based high-temperature alloy GH3536, the nickel-based high-temperature alloy GH3536 is used as the matrix material, and the heating and heat preservation process is 950° C. and the heat preservation is 4 hours.

[0033] The hardness of the base material was tested by Rockwell hardness measurement, that is, the hardness before strengthening was 14.4HRC. The results are shown in Table 1.

[0034] The corundum crucible container filled with strengthening agent and matrix material is as follows: Figure 1 The strengthening agent specifically includes 12% B4C, 53% KBF4, 15% SiC and 20% graphite.

[0035] After heating and heat preservation, the corundum crucible was unsealed and the sintered material on the sample surface was removed by grinding with a grinder. The morphology of the surface-strengthened sample was as follows: Figure 2 As shown. The thickness is about 1mm.

[0036] The surface strengthened sample was subjected to Rockwell hardness test, that is, the hardness after strengthening was 58.6HRC. The results are shown in Table 1.

[0037] Embodiment 2:

[0038] Cobalt-based high-temperature alloy GH5188 is used as the matrix material, and the heating and insulation process is 950°C and insulation for 4 hours.

[0039] The hardness of the base material was tested by Rockwell hardness measurement, and the results are shown in Table 1.

[0040] The corundum crucible container filled with strengthening agent and matrix material is as follows: Figure 1 The strengthening agent specifically includes 11% B4C, 52% KBF4, 16% SiC and 21% graphite.

[0041] After heating and heat preservation, the corundum crucible was unsealed and the sintered material on the sample surface was removed by grinding with a grinder. The morphology of the surface-strengthened sample was as follows: Figure 2 As shown. The thickness is about 0.7mm.

[0042] The surface hardness test results are shown in Table 1.

[0043] Embodiment 3:

[0044] Cobalt-based high-temperature alloy GH3536 is used as the matrix material, and the heating and insulation process is 1050°C and insulation for 5 hours.

[0045] The hardness of the base material was tested by Rockwell hardness measurement, and the results are shown in Table 1.

[0046] The corundum crucible container filled with strengthening agent and matrix material is as follows: Figure 1 The strengthening agent specifically includes 11% B4C, 52% KBF4, 15% SiC and 22% graphite.

[0047] After heating and heat preservation, the corundum crucible was unsealed and the sintered material on the sample surface was removed by grinding with a grinder. The morphology of the surface-strengthened sample was as follows: Figure 2 As shown. The thickness is about 0.5mm.

[0048] The surface hardening samples were subjected to room temperature Rockwell hardness tests, and the results are shown in Table 1.

[0049] The sample that has completed the strengthening treatment in Example 1 and the unstrengthened sample (GH3536) of the same specification were used to conduct an oxidation weight gain test at 800°C and keep warm for 5 hours. The test results are shown in Table 3.

[0050] Table 1 Hardness of base material and hardness of surface strengthening material under various embodiments

[0051] Hardness before strengthening / HRC Hardness after strengthening / HRC Example 1 14.4 58.6 Example 2 35.3 58.2 Example 3 35.3 66.7

[0052] Table 2 High temperature oxidation weight gain test results under Example 1

[0053] Specimen type Before weight gain / g After weight gain / g Increase Example 1 64.90 64.91 0.015% GH3536 alloy 67.80 67.88 0.118%

[0054] In summary, the present invention can obtain a high-performance strengthening surface layer with a thickness of 0.5-1mm and a hardness of 58HRC or more by strengthening the surface of the base material. Compared with similar process technologies, the thickness and hardness of the strengthening layer are at a significantly leading level. After the alloy has the strengthening layer, it has both the excellent strength of the high-temperature alloy and the high hardness and excellent wear resistance of the metal-based wear-resistant material, and the high-temperature oxidation resistance is further improved. In addition, compared with the existing similar treatment processes, the present invention has a simple component composition, low toxicity, high safety, and is suitable for all alloys containing Fe, Cr or Mo elements including high-temperature alloys. The strengthening treatment process is easy to operate, and no protective atmosphere is required. It can be carried out only in the atmospheric atmosphere. The base material does not need to be finely processed and pre-treated such as fine grinding and polishing before treatment. It can be carried out after simply cleaning the surface. The workpiece after strengthening treatment does not need to be further heat treated. It has a wide range of applications and is very suitable for the preparation of tools and equipment under various high-temperature underground complex load and wear conditions such as underground coal gasification, heavy oil thermal recovery, and geothermal mining.

[0055] Composition analysis of the reinforcement layer:

[0056] The energy spectrum analysis of the strengthening layer of Example 1 is performed, as shown in FIG. Figure 3 As shown, it can be seen that the main components are Fe, Cr, Mo, Ni, and B.

[0057] High temperature airborne particle erosion and wear performance test:

[0058] The reinforced sample obtained in Example 1 and the unreinforced GH3536 sample were tested, and the specific test method is as follows:

[0059] Table 3 gives the test parameters of high-temperature airborne particle erosion and wear. The test adopts a high-temperature, high-speed airflow small-angle erosion test method. The shape, size, and type of the erosion particles used in the test are all irregularly designed to fully simulate the complex working conditions underground. Before the test, the sample of Example 1 and the sample of GH3536 are first weighed, recorded as M1 and M2. In the test container, the sample is tilted according to the test erosion angle. After the test container is heated to the test temperature, the high-temperature gas mixed with erosion particles is filled into the upper pipe of the container at the test gas flow rate, and it continues until the test time is reached. After the test, the sample is weighed twice, recorded as m1 and m2.

[0060] Table 3 Example 1, GH3536 alloy high temperature airborne particle erosion wear test plan

[0061]

[0062]

[0063] Table 4 shows the high temperature airborne particle erosion and wear test results of Example 1 and GH3536 sample.

[0064] Table 4: Experimental results of high temperature airborne particle erosion and wear test on GH3536 alloy in Example 1

[0065] Sample No. Example 1 GH3536 Mass before test M / g 97.4607 108.8589 Mass after test m / g 97.4328 108.7016 Mass loss Δm / g 0.0279 0.1573

[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A ceramic-based surface strengthening agent for underground coal gasification downhole tools, characterized in that: The invention comprises the following components in mass fractions: the mass fraction of a boron supply agent is 8.7%-14.7%, the mass fraction of an activator is 49.7%-55.7%, the mass fraction of a filler is 11.6%-17.6%, and the mass fraction of a reducing agent is 18.0%-24.0%.

2. The ceramic-based surface strengthening agent for underground coal gasification downhole tools according to claim 1, characterized in that: The boron supplying agent is B4C.

3. The ceramic-based surface strengthening agent for underground coal gasification downhole tools according to claim 1, characterized in that: The activator is KBF4.

4. The ceramic-based surface strengthening agent for underground coal gasification downhole tools according to claim 1, characterized in that: The filler is SiC, SiO2 or Al2O3.

5. The ceramic-based surface strengthening agent for underground coal gasification downhole tools according to any one of claims 1 to 4, characterized in that: The reducing agent is graphite or activated carbon.

6. A method for strengthening an alloy matrix, characterized in that: The method comprises the following steps: wrapping the alloy matrix with the ceramic-based surface strengthening agent for underground coal gasification downhole tools according to any one of claims 1 to 5, and then heating and keeping the temperature at 950-1050° C. for 3-5 hours.

7. The method for strengthening the alloy matrix according to claim 6, characterized in that: The alloy matrix is ​​a nickel-based high-temperature alloy, a cobalt-based high-temperature alloy or a heat-resistant steel.

8. A material strengthened by the method according to claim 6 or 7, characterized in that: It includes alloy matrix and surface strengthening layer.

9. The material according to claim 8, characterized in that: The strengthening layer includes a high-hardness metal compound M2B formed by B and Fe, Cr or Mo elements, where M is Fe, Cr or Mo element.

10. The material according to claim 8, characterized in that: The thickness of the strengthening layer is 0.5-1mm; The hardness of the strengthening layer is greater than or equal to 58HRC.